2014
DOI: 10.1103/physrevb.89.201117
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Ce valence in the coexistence of superconductivity and ferromagnetism ofCeO1xFxBiS2revealed by CeL

Abstract: We have performed Ce L3-edge x-ray absorption spectroscopy (XAS) measurements on CeO1−xFxBiS2, in which the superconductivity of the BiS2 layer and the ferromagnetism of the CeO1−xFx layer are induced by the F-doping, in order to investigate the impact of the F-doping on the local electronic and lattice structures. The Ce L3-edge XAS spectrum of CeOBiS2 exhibits coexistence of 4f 1 (Ce 3+ ) and 4f 0 (Ce 4+ ) state transitions revealing Ce mixed valency in this system. The spectral weight of the 4f 0 state decr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 35 publications
11
57
0
Order By: Relevance
“…In addition to the three main features, there is a weak structure around 5.75 keV. This is the typical structure of layered rareearth system, and its intensity is sensitive to the O/F atomic order/disorder in Ce(O,F) layer 22 . All the XAS results are quantitative consistent with the previous Ce L 3 -edge XAS results of polycrystalline CeO 1−x F x BiS 2 22 .…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the three main features, there is a weak structure around 5.75 keV. This is the typical structure of layered rareearth system, and its intensity is sensitive to the O/F atomic order/disorder in Ce(O,F) layer 22 . All the XAS results are quantitative consistent with the previous Ce L 3 -edge XAS results of polycrystalline CeO 1−x F x BiS 2 22 .…”
mentioning
confidence: 99%
“…Among the various REO 1−x F x BiS 2 compounds, CeO 1−x F x BiS 2 is very unique in that the superconductivity in the BiS 2 layer and the ferromagnetism in the CeO 1−x F x layer coexist for x > 0.4 21 . Meanwhile, an x-ray absorption spectroscopy (XAS) study on CeO 1−x F x BiS 2 has revealed that the Ce valence is intermediate (valence fluctuation) and the Ce 4f states may contribute to the Fermi surfaces for x < 0.4, and the F-doping makes the system crossover from valence fluctuation regime to Kondo-like regime 22 . However, from the DC susceptibility measurement on CeOBiS 2 , Ce 4f electrons are found to be in a well-localized state 23 , which is inconsistent with the XAS results.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is also possible that the valence number of rare earth elements with f electrons in the blocking layer changes as a function of F concentration as reported in x-ray absorption spectroscopy measurement of Ce(O,F)BiS 2 (Ref. [39]). On the other hand, the observed FS shape as well as the band dispersion on La(O,F)BiS 2 is in good accordance with the predicted bands for nominal x value, thus the La(O,F)BiS 2 system is likely to be free from such complications.…”
mentioning
confidence: 99%